Draft Genome Sequence of a Multi-Metal Resistant Bacterium Pseudomonas Putida Ath-43 Isolated from Greenwich Island, Antarctica - Vasquez-Guzman, C; Muñoz-Diaz, P (Frontiers Media S.A., 2016)
Sin Resumen Disponible
Keywords: Pseudomonas putida; multi-metalresistance; mercury; tellurite; psychrotroph; Antarctica